YAG Laser Capsulotomy Complication - Riddhi Thaker; Ahmed Shalaby Bardan; Bassma Al-Baioumy; Ahmed AR Souka (International Journal of Medical Science and Clinical Research Studies, 2024)
A 41-year-old presented with unilateral painful eye, with reduced vision since a YAG laser procedure. This was carried out by a local ophthalmologist when she presented with hazy vision in the right eye and gave a previous history of lens implantation.